Study on the application value of histogram parameters from reduced field-of-view VOI in rectal cancer. - Zhang, Yumeng; Fan, Rui; Cao, Yuntai (Abdominal Radiology, 2026)
Purpose: To establish a reduced field-of-view (rFOV) DWI protocol on a 3.0T high-field MRI platform, explore the correlation between ADC histogram parameters derived from rFOV VOI and rectal cancer T/N staging, lymphatic vessel invasion, peripheral nerve invasion, histological differentiation, and Ki-67. Methods: Prospectively included 47 pathologically confirmed rectal adenocarcinoma patients (March 2023-December 2024) for analyzing rFOV VOI histogram parameters. FireVoxel extracted ADC histogram parameters from tumor VOIs. Spearman correlation assessed relationships between parameters and T/N staging, lymphatic vessel / peripheral nerve invasion, histological differentiation, and Ki-67. ROC curves evaluated diagnostic efficacy. Results: T-stage linked to Max, Min, Perc.1%, Perc.5%, Perc.10%, Perc.25% (P < 0.05); N-stage to Max, Min, Variance, Skewness, Kurtosis, Perc.99%; lymphatic vessel invasion to Max, Kurtosis, P99% (highest AUC: 0.773, combined diagnosis); peripheral nerve invasion to Max, Variance, Skewness, Kurtosis, Perc.95%, Perc.99% (highest AUC: 0.921, combined diagnosis); histological differentiation to Max, Variance, Skewness, Kurtosis, Perc.90%, Perc.95%, Perc.99% (highest AUC: 0.824, combined diagnosis); Ki-67 to Variance, Skewness, Perc.90%, Perc.95%, Perc.99% (highest AUC: 0.814, combined diagnosis). All P < 0.05. Conclusions: ADC histogram analysis based on rFOV VOI reveals correlations between histogram parameters and pathological features of rectal cancer, highlighting their potential value as imaging biomarkers for staging and prognosis.